Adverse events reporting in stage III NSCLC trials investigating surgery and radiotherapy. Issue 3 (14th September 2020) - Iseli, Thomas; Berghmans, Thierry; Glatzer, Markus; Rittmeyer, Achim; Massard, Gilbert; Durieux, Valérie; Buchsbaum, Thomas; Putora, Paul Martin
Background: Current treatment options for stage III non-small cell lung cancer (NSCLC) consist of different combinations of chemotherapy, surgery, radiotherapy and immunotherapy. Treatment choices are highly individual decisions, in which adverse events (AEs) are relevant for decision-making. This study aims to analyse reporting of AEs in prospective stage III NSCLC trials, focussing on trials including radiotherapy and/or surgery. Methods: PubMed was searched for prospective studies dealing with stage III NSCLC from January 1987 to April 2019. Meta-analyses were screened as a positive control. Pearson's Chi-squared test and smooth kernel distribution were used to estimate distributions. Data was resampled using bootstrapping. Results: Out of 1193 initially identified studies, 119 met the inclusion criteria. Of these, 31 had a surgical procedure in any study arm. Grade 3 and 4 AEs were reported in 94.12% and 92.44% of the included studies, respectively. Reporting of grade 5 AEs was provided in 87.39% of cases. Grade 1 and 2 AEs were less commonly reported at 53.78% and 63.03%, respectively. One study did not mention any AEs. Of the 31 treatment arms including any form of surgery, AEs were not reported in 10. Overall, 231 different AE items were reported, only 18 of them were included in at least 20% of the analysed studies. Conclusion: Overall, AE reporting in stage III NSCLC was inconsistent and inhomogeneous. Studies including surgical study arms often reported only treatment-related deaths in regards of surgical AEs. Underreporting of AEs prohibits the extraction of patient-relevant information for decision-making and represents a suboptimal use of invested resources. Adverse event reporting for stage III NSCLC is inconsistent and inhomogeneous. Surgical studies tend to underreport lower grade adverse effects. Patient-relevant information for decision-making is lost and invested resources are used suboptimally. https://bit.ly/3gLNIYy